2015
DOI: 10.2337/db14-0509
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics and Diabetes: Analytical and Computational Approaches

Abstract: Diabetes is characterized by altered metabolism of key molecules and regulatory pathways. The phenotypic expression of diabetes and associated complications encompasses complex interactions between genetic, environmental, and tissue-specific factors that require an integrated understanding of perturbations in the network of genes, proteins, and metabolites. Metabolomics attempts to systematically identify and quantitate small molecule metabolites from biological systems. The recent rapid development of a varie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
122
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(123 citation statements)
references
References 136 publications
0
122
0
1
Order By: Relevance
“…Several techniques have been developed to survey molecular alteration to clarify the pathogenesis of diseases (11). One of the powerful tools in biomarker discovery is metabolomics that can illuminate the underlying biology and discover clinical markers of diseases us-ing bioinformatics pathway analysis (12). In recent years, some metabolomics studies in biomarker discovery have been reported on various diseases by our group (13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…Several techniques have been developed to survey molecular alteration to clarify the pathogenesis of diseases (11). One of the powerful tools in biomarker discovery is metabolomics that can illuminate the underlying biology and discover clinical markers of diseases us-ing bioinformatics pathway analysis (12). In recent years, some metabolomics studies in biomarker discovery have been reported on various diseases by our group (13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…Another unsupervised method for this purpose is the Hierarchical Cluster Analysis (HCA) (8,44). The most used supervised classification methods are k-nearest-Neighbors (kNN) (1,38), Soft Indipendent Modeling of Class Analogy (SIMCA) (12) and Partial Last Squares Discriminant Analysis (PLS-DA) (3,14). The supervised method use the sample class as a variable for establish discrimination rules.…”
Section: Chemometrics (Statistical Analysis)mentioning
confidence: 99%
“…This technology enables the measurement of various metabolites present in all organisms and provides new risk markers of T2DM and clinical efficacy by indicating the overall drug response index [16][17][18]. Identification of small molecular metabolites in bodily fluids will enable determination of drug effectiveness and prediction of treatment according to the phenotype of patients.…”
Section: Introductionmentioning
confidence: 99%